2016
DOI: 10.2306/scienceasia1513-1874.2016.42.159
|View full text |Cite
|
Sign up to set email alerts
|

Beach forest changes (2003–2013) in the tsunami-affected area of Phang Nga, Thailand from multi-temporal satellite data

Abstract: Beach forests are important ecological zones in many coastal regions. Many are under increasing anthropogenic and natural stress. Beach forest changes and their causes were examined in three tsunami-impacted sites with different land-use/cover (LULC): Ban Nam Khem (BNK, fishing village), Khao Lak (KL, tourist destination), and Thai Mueang (TM, part of a national park). Vegetation surveys, GIS, and interpretation of time series IKONOS and THEOS imagery using supervised classification (ENVI 4.7) from 2003-2013 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The geological profile of available raw material across the shoreline is predominantly limestone, with the occasional rock formed of igneous rocks such as granite cobbles, which do not occur naturally on the Islands but may have been transported to the islands by wave action. There are occasional granite outcrops in other areas within Phang Nga bay (Charusiri et al, 1993), and this is a tsunami prone region (Kongapai et al, 2016) which could transport stone material to the research sites.…”
Section: Methodsmentioning
confidence: 99%
“…The geological profile of available raw material across the shoreline is predominantly limestone, with the occasional rock formed of igneous rocks such as granite cobbles, which do not occur naturally on the Islands but may have been transported to the islands by wave action. There are occasional granite outcrops in other areas within Phang Nga bay (Charusiri et al, 1993), and this is a tsunami prone region (Kongapai et al, 2016) which could transport stone material to the research sites.…”
Section: Methodsmentioning
confidence: 99%
“…The number of beach forest plants in San Agustin, Romblon was relatively higher than in other beach forests in the Philippines and other countries (Table 4). For instance, only 16 species were found on Dinagat Island (Lillo et al, 2019), 21 species were found on Sicogon Island (Pedregosa et al, 2006), and 24 species were found in Pang Nga, Thailand (Kongapai et al, 2016). On the other hand, the results of the present study were lower compared to the study of Sabulao et al (2020) in Guiuan Eastern Samar with 39 species, a study by Garcia et al (2017) in Surigao, the Philippines, with 55 species, study of Nini and Tatil (2017) in Surigao del Norte with 57 species and the study of Neamsuvan et al (2012) in Songkhla province, Thailand with 69 species.…”
Section: Species Richness Diversity Dominance and Evenness Of Beach F...mentioning
confidence: 99%
“…These are critical ecological zones in many coastal regions. Plant species in these zones are adapted for growing in harsh environmental conditions, experiencing wide variations in temperature, salinity, and humidity which influence the composition of plant species (Cochard et al, 2008;Kongapai et al, 2016). They are also resilient to wind, rain, waves, and salt sprays from the ocean (Tanaka et al, 2007;Cochard et al, 2008;Kongapai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations